The Effectiveness of a Training Program for Mathematics Teachers Based on the Criterion of Mathematical Communication in the Achievement and Development of Mathematical Communication Skills among Middle School Students in the Kingdom of Saudi Arabia - Bin Jahlan, Abdullah (Dirasat: Educational Sciences, 2021)
This study aims to identify the effectiveness of a training program for mathematics teachers based on the criterion of mathematical communication on achievement and development of mathematical communication skills among middle school students in the Kingdom of Saudi Arabia. The study used the quasi-experimental approach, and the study sample consisted of (554) students from the second intermediate grade in ten schools that were selected in a way. Intentionally, in government schools affiliated to the General Administration of Education in Jeddah Governorate, twenty study divisions were distributed randomly into two groups, one experimental consisting of (277) students and the other control consisted of (277) students, and to achieve the objectives of the study, the researcher prepared a training program for mathematics teachers based on Mathematical communication standard, a pre- and post-achievement test was prepared for students, and the results of the study showed statistically significant differences at (α = 0.05) between the mean scores of the study individuals in achievement in favor of the experimental group students, the results also indicated that there were statistically significant differences at (α = 0.05) between the mean scores of the study individuals in the test of mathematical communication skills in favor of the experimental group students.